Worldwide interconnections of Africa using crops as historical and cultural markers - (:unkn) unknown (My University, 2019)
The historical, social, and economical importance of precolonial connections between Africa and the rest of the world has been undervalued. In the present study, we use crops as historical and social markers to analyze intercontinental connections from the perspective of Kenyan and Ugandan regions northeast of Lake Victoria. Crops were inventoried in 148 small farms from 74 localities, using successively free listing, to reveal their socio-cultural salience, and a closed list method, for a more complete picture of the agricultural, environmental and social diversity. The total sample included 75 crops (30 African, 21 Asian, 21 American, and 3 European). Among farms, crop richness varied from 6 to 32. It was higher in Uganda than in Kenya, and lowest around the Winam Gulf. The 12 American crops introduced at Renaissance were uniformly distributed, and the observed structure was mostly due to differences in African and Asian crop richness. In terms of crop frequency, exotic crops account for 74%, with 46% for American crops. The 14 most frequent crops included 10 from America, 3 from Asia, and 1 for Africa, with negligible differences among linguistic groups. Consistently, the free listing citation order demonstrated the high cultural salience of American crops. The spatial distribution of minor crops suggest differential diffusion among linguistic groups, which could be further studied using linguistic approaches on crop names.
Keywords: African Research